Collective Experiences, Individual Interpretations (KULT_online, 2019)
In The Audience Effect, Julian Hanich examines the effects people have on each other’s experiences inside the movie theater. Through a phenomenological approach, the author creates powerful descriptions of these experiences and the possible ways they might affect reception of the movie. Hanich’s argumentation is sustained by several previous studies while he discusses in particular the laugh, the cry, and the anger, and presents a typology of collective viewing. The book shows that the spectators’ behavior and cinema infrastructures contribute to our interpretation and evaluation of a movie, as well as an ongoing unique experience in the movie theater. An essential read for those interested in film reception.